A phenomenological study of the experiences of black nurses through the menopause - Chard, Diana Alexandria (My University, 2014)
The purpose of this study was to examine, from a subjective point of view, the experiences and meanings of menopause by black nurses. In South Africa the biomedical model of menopause, which portrays menopause as a deficiency disease requiring medical treatment, is the model that dominates the media, and medical thought. The narrow confines of this model leave no room for any explanation for the richness of experiences that women may have at this time, nor does it have any scope for the contributions of the socio-cultural, psychological and spiritual influences that may impact on a woman's life at this time. This study aimed to explore the actual experiences of women at this time - in this instance black nurses. Eight respondents were interviewed and the transcribed interviews were analysed in order to extrapolate categories, themes and sub-themes. These were then cross-analysed for similarities and disparities. Themes and categories were illustrated by means of verbatim excerpts from the transcribed interviews. A literature search was undertaken to validate the results and findings. Bodily changes, psychological aspects, social relationships and "becoming" emerged as the central themes; cessation of menses, discomfort, health seeking behaviour, seeking knowledge, anxiety/fears, emotional tone, relationships and existential and spiritual aspects also were apparent. These were explored for their impact on the experience of menopause. The experience of menopause as described by the respondents does not fit neatly into the biomedical model. Rather, there emerges a richness of experience that is expected to lead to a fulfilling future, although this is tempered by fears and anxieties related to marital abandonment, feeling "less than a woman" and of cancer. Social relationships were important at this time, and difficulties with partners were highlighted, as was irritability with children, and to a lesser extent, with colleagues. However, while it was culturally unacceptable to talk to their mother's about menopause, respondents talked to colleagues, and these and other friends were perceived as generally being more helpful and supportive than husbands and partners. One of the most important findings to come from this research is that there is a great need for accurate '^formation about menopause to be made available to women. While the sample is too small for generalisation, confirmation of these findings by other studies would have implications for health service policies.
Thesis (M.Sc.Nursing)--University of the Witwatersrand, Faculty of Health Sciences, 1998.